Riding with dogs in cars: What can it teach us about transport practices and policy?. (December 2017) - Kent, Jennifer L.; Mulley, Corinne
Highlights: Dog ownership is a health promoting practice. Dog owners travel often with dogs in private cars. Allowing pets on public transport has potential to discourage dog-related car trips. Allowing pets on public transport may help normalise public transport use in car dependent cities. Abstract: In low density cities shaped by the assumption of private car access and a relative paucity of public transport options, it is likely there are personal costs to not having a car. These subtle sacrifices contain vital clues as to why many people remain attached to car use, and their exposure can inform policy solutions that encourage car independence. This paper takes dog ownership as a case in point of an ostensibly health promoting and personally satisfying practice which, in many cities, either requires, or is enriched by, access to a private car. Drawing on empirical data from a convenience survey of over 1250 dog owners in Sydney, Australia, we explore the way cars augment and shape the human-dog bond and identify a high level of car use for dog-related trips. This suggests a distinct and previously unrecorded inclination for people to travel relatively long (that is, non-walkable) distances with their dog. It also reflects the fact dogs are prohibited on the public transport network in our case study city, leaving no legal alternative but to drive non-walkable dog-related trips. Enabling dogs to ride public transport with their owners is suggested as a potential way to reduce dog-related car trips, while fulfilling preferences for owners to travel with their dogs. Unsurprisingly, survey participants indicated nigh universal support for such policies, with many stating they would change their transport behaviour should such a policy be approved. Given the support and benefits of allowing dogs on public transport, the second part of the paper explores how such initiatives are regulated across the developed world and considers the practical and cultural implications of pursuit of such a policy in a car-dominated city. We conclude with reflections on lessons to be learned from differences in dogs-on-transport policy and practice from city to city. We explore whether such differences indicate the normalisation and acceptance of public dogs, or public transport.